2015
DOI: 10.1007/s10616-015-9846-0
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal expression of Prdm genes during Xenopus development

Abstract: Epigenetic regulation is known to be important in embryonic development, cell differentiation and regulation of cancer cells. Molecular mechanisms of epigenetic modification have DNA methylation and histone tail modification such as acetylation, phosphorylation and ubiquitination. Until now, many kinds of enzymes that modify histone tail with various functional groups have been reported and regulate the epigenetic state of genes. Among them, Prdm genes were identified as histone methyltransferase. Prdm genes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Intriguingly, Prdm14 is expressed in the neuronal system in amphioxus, zebrafish and Xenopus embryos (Eguchi et al, 2015), and is required for motor neuron maturation in zebrafish embryos (Liu et al, 2012). The CBFA2T family is also expressed in the neural system in Xenopus and chicken embryos, and its expression is involved in neurogenesis, including motor neurons (Cao et al, 2002;Aaker et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, Prdm14 is expressed in the neuronal system in amphioxus, zebrafish and Xenopus embryos (Eguchi et al, 2015), and is required for motor neuron maturation in zebrafish embryos (Liu et al, 2012). The CBFA2T family is also expressed in the neural system in Xenopus and chicken embryos, and its expression is involved in neurogenesis, including motor neurons (Cao et al, 2002;Aaker et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in chick embryos showed that Prdm1 undergoes stage-specific binding to regulatory regions of neural and sensory progenitor genes in early neural plate and sensory progenitor cells (Prajapati et al, 2019). Prdm1 was also established to have a role in histone modification in Xenopus, having DNA binding ability and methylation activity throughout neural cell differentiation processes (Eguchi et al, 2015). This particular gene limits the function of the gastrula organizer and in turn regulates morphogenetic development and cell fate specification during early axes-determining stages (Wilm & Solnica-Kerzel, 2005).…”
Section: Significant Roles Of the Downstream Significant Roles Of The Downstream Targets In Ear Formation Targets In Ear Formation Prdm1 mentioning
confidence: 99%
“…eya2 is expressed in the pre-placodal region and acts as a Six1 cofactor to promote PPE gene expression and suppress neural plate and neural crest cell fates [ 29 , 44 , 45 ]. prdm1 (aka blimp1 ) encodes a transcription factor that plays a role in pharyngeal arch, neural crest and placode formation [ 46 , 47 , 48 , 49 ]. spry1 encodes a negative regulator of FGF signaling and is expressed in several craniofacial tissues [ 50 , 51 , 52 ].…”
Section: Introductionmentioning
confidence: 99%